Longitudinal assessment of PTSD and illicit drug use among male and female OEF-OIF veterans. (July 2021) - Livingston, Nicholas A.; Lee, Daniel J.; Mahoney, Colin T.; Farmer, Stacey L.; Cole, Travis; Marx, Brian P.; Keane, Terence M.
Highlights: PTSD predicted future drug use and related problems among veteran men only. Drug use problems predicted future PTSD symptom severity among veteran women. Drug use and PTSD were most strongly correlated among drug using veteran women cross-sectionally. Abstract: Objectives: Posttraumatic stress disorder (PTSD) and substance use share both directional ("self-medication") and mutually-reinforcing associations over time. Research on gender differences regarding the co-occurrence of PTSD and substance use over time remains limited and largely focused on alcohol use; less is known regarding the co-occurrence of PTSD and illicit drug use, especially among veteran men vs. women. As the proportion of women in the military expands, we believe a greater focus on gender differences is warranted. Method: We conducted a cross-lagged panel analysis of PTSD symptoms and drug use problems using two waves of data from a large, nationwide longitudinal registry of post-9/11 veterans. Participants included 608 men and 635 women ( N = 1243; Mage = 42.3; 75.2% White) who completed self-report PTSD and drug use problem questionnaires at T1 and again at T2 15–37 months later. Results: Veteran men reported more severe drug use and related problems overall, yet the cross-sectional correlation between PTSD and drug use problems was strongest among drug using veteran women. In our cross-lagged models, we found that PTSD symptoms predicted future drug use problems among veteran men, whereas drug use problems predicted future PTSD symptom severity among women. Conclusions: These results support the self-medication pathway among veteran men but not women, for whom drug use problems might prolong or exacerbate PTSD symptom severity over time. These results are consistent with some emerging evidence but also provide novel insight into functional associations governing the longitudinal course of PTSD and drug use problems for men vs. women.